A simple mathematical model for the legal concept of balancing of interests - Frederike Zufall; Rampei Kimura; Linyu Peng (Max Planck Institute for Research on Collective Goods, 2021)
We propose simple mathematical models for the legal concept ofbalancing of interests, to resolve the conflict between the rights toprivacy and to the protection of personal data in Art. 7 and Art. 8 ofthe EU Charter of Fundamental Rights (EUCh) against the right ofaccess to information derived from Art. 11 EUCh. These competing rights are denoted by (i1) privacy of information and (i2) access to information; mathematically, their indices are respectively assigned by u1=[0,1]and u2=[0,1]subject to the constraint u1+u2=1.This constraint allows us to use one single index u to resolve the conflict through balancing. The outcome will be concluded by comparing the index u with a prior given threshold u0. For simplicity,we assume that the balancing depends on only selected legal criteria such as the social status of affected person, and the sphere from which the information originated, which are represented as inputs of the models, called legal parameters. Additionally, we take "time" into consideration as a legal criterion, building on the European Court of Justice's ruling on the right to be forgotten: by considering time as a legal parameter, we model how the outcome of the balancing changes over the passage of time. To catch the dependence of the outcome u by these criteria as legal parameters, data were created by a fully-qualified lawyer. Two mathematical models for u, a time-independent model and a time-dependent model, are proposed, that are fitted by using the data.
hdl:21.11116/0000-0008-6ABD-D
Keywords: 330; Rechtsprechung; Rechtsökonomik; Mathematik; Modellierung; Datenschutz; Informationsfreiheit; Theorie